INTERNATIONAL TRADE WITH ONIONS - Radu Lucian PÂNZARU; Dragoş Mihai MEDELETE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2013)
The paper refers to the global trade situation with onion, 2008-2010. Besides presenting the existing situation of the five units continents (Africa, America, Asia, Europe and Oceania) study shows worldwide level of imports and exports, as well as its contribution to the performing acts of international exchange. Quantitative aspects of trade are filled with values data, that allowed the preparation of trade exchanges for this product. The main importer (in quantitative terms) is represented by Asia, followed by Europe and at greater distance by the America, while the value of imports was dominated by operations performed in Europe, Asia and America - weights of 39.7 , 38.1 and 18.6% respective (of the world total). Concerning the quantity, the major players on the market exports are represented by Asia and Europe. They have dominated the world market, achieving 45.6 and respective 30.8% of world exports. America ranks third with a share of 17.4%. In terms of value, world exports were dominated by Asia, Europe and America (33.5, 32.7 and respective 26.7%), with a downward trend in the share of Asia and increasing European weights and American (compared to the specific situation of the quantities exported)